Pengaruh Earning Persistence, Leverage, Profitability dan Firm Size Terhadap Earning Response Coefficient - Fahreza Ihwan Nur Ardiansyah,; Ovi Itsnaini Ulynnuha, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Earning response coefficient (ERC) is a measure of how much abnormal stock return will be obtained by responding to unexpected earnings as profit information published by the company. The purpose of this study was to test and analyze the effect of earnings persistence, leverage, profitability and firm size on the earning response coefficient (ERC) in consumer goods sector companies consisting of primary and non-primary consumer goods companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sampling technique in this study used purposive sampling technique. A total of 82 companies have met the requirements as research objects so that the total sample used is 246 samples. The analysis method used in this study is the multiple linear regression analysis method. The results of the study show that the variables that affect the earning response coefficient are earning persistence. While leverage, profitability and firm size do not affect the earning response coefficient.